A high-efficiency salt-rejecting solar evaporator with optimized porous structure for continuous solar desalination. (25th March 2021) - Huang, Qiangqiang; Du, Changkang; Guo, Chuwen; Huang, Congliang; Wang, Xiaodong
Highlights: Crystalline salts can severely weaken the evaporator performance. The good salt-rejecting property comes from the high porosity and large pores. System achieves high-efficient self-cleaning operation in the high-salinity brine. High evaporation efficiency of the evaporator benefits from salt rejection. Abstract: Solar interfacial evaporation technology has been advanced rapidly in recent years due to its high efficiency and environment friendliness. However, the salt accumulation in the evaporation surface severely limits the stable evaporation performance of interfacial evaporator, especially for high-salinity brine. Here, we prepared a salt-rejecting solar evaporator with carbon blacks deposited on the super-hydrophilic polystyrene/lignocellulose (PS/LF) skeleton. By analyzing the factors that affect antifouling ability of evaporators, like the skeleton porosity and pore size, we obtained a continuous salt-rejecting porous structure with the porosity of about 70.4% and the pore size of 150–300 μm. This evaporator with optimized porous structure could achieve continuous salt rejection in the high-salinity environment (15% NaCl), and exhibit a stable evaporation rate of 1.90 kg·m −2 ·h −1 and a high evaporation efficiency of 85.5% under a 1.5-sun irradiation. The good salt-rejecting property comes from the high porosity of evaporator which means numerous water channels to promote salt exchange, and large pores which means large hydraulic diameter and small tortuosity of pore channels to shorten the migration distance of salt ions back to bulk water. These two factors together promote the rapid reflux of salt ions, enabling the continuously self-cleaning of evaporator. Given the salt accumulation on the surface could contaminate the sunlight absorption, the high evaporation efficiency of the evaporator benefits from the salt rejecting. At the same time, the thermal insulation structure which was used to support the evaporator further ensures the high evaporation efficiency.